Improving augmented reality applications with optical flow - Herakleous, Kyriakos; Poullis, Charalambos (My University, 2013)
This paper presents an augmented reality application framework which does not require specialized hardware or pre-calibration. Features extracted, using SURF, are matched between consecutive frames in order to determine the motion of the detected known object with respect to the camera. Next, a bi-directional optical flow algorithm is used to maintain the performance of the system to real-time. The system has been tested on two case studies, a children's book and advertisement, and the results are reported.
Keywords: Augmented reality; Marker-less tracking